Peningkatan Usaha Koperasi Wisata Berbasis Potensi Desa - Kartika, Neng Evi; Syafrudin, Oding (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2023)
The village environment in West Java presents beautiful and enchanting natural views. This natural potential can be managed in such a way that it can improve the regional economy. Management can be done through economic institutions, such as cooperatives with a specific business unit, namely tourism or Tourism Cooperatives. This community service activity aims to increase understanding of running a business through legal entity tourism cooperatives, developing tourism cooperative businesses, assisting with the legality of cooperative institutions, and assisting in obtaining business permits through online single submission (OSS). This activity uses the participatory rural appraisal (PRA) method to make conducting community economic business development activities based on village potential easier. The result of this activity is that the cooperative management community has a tourism business development plan document in accordance with the KBLI, strategic plan, work plan, and follow-up to each business development program. Tourism Cooperatives already have complete legality accompanied by various business permits such as Notarial Deeds, Ministry of Law and Human Rights Deeds, Business Permit Numbers (NIB), and Licensing for each business unit owned, with adequate cooperative organizational structure and completeness.